The Moderating Effect of Interest Rates and Inflation on the Effect of Bond Coupons and Bond Maturity on the Price of Fixed Rate (FR) Series RI State Bonds in 2022 - Indreswati, Megawati; Lumbantobing, Rudolf; Purnama, Desy Eka (GoAcademica Research & Publishing, 2024)
This study examines the moderating effect of Interest Rate and Inflation on the effect of Bond Coupon and Bond Maturity on the Price of FR Series Government Bonds in 2022. In addition, this study aims to see if there are differences in the effect of Bond Coupons, and Bond Maturity on Bond Prices in the presence of moderating effect factors of Interest Rates and Inflation in 2022. This study examines the impact of the moderating effects of interest rates and inflation that affect the changes in bond prices that occur by looking at the Bond Coupon and Bond Maturity factors. With the method used, the experimental hypothesis is quantitative, and the data is obtained from www.bps.go.id, www.bi.go.id, and www.idx.co.id. The analysis method used was purposive sampling, and the SPSS version 26 computer program was used. The results of data processing and analysis show that Bond Coupon Bond Coupons have a significant positive impact on Bond Prices. When the size of the Bond Coupon owned will affect the Bond price and the effect of Bond Maturity on Bond Price is negative and insignificant. Until now, there has not been enough evidence to support the first hypothesis that bond maturity will have a positive impact on Bond Prices. Moderating Effect of BI Rate Interest Rate Data. Against bond maturity and bond coupons on bond prices by adding the moderating effect of BI Rate data, it makes the BI Rate data negative and insignificant.